Quichotte [compact disc, unabridged] : a novel - Rushdie, Salman (Random House Audio, an imprint of the Penguin Random House Audio Publishing Group, 2019)
In a modern adaptation of "Don Quixote," a courtly, addled salesman embarks on a cross-country journey with his imaginary son Sancho to find and convince a television star of his love for her.